Peculiarities of Training Physicists in Universities Abroad - Luniachek, O. (Problems of Engineer-Pedagogical Education, 2019)
The paper highlights peculiarities of the vocational training process in the field of physics for postBachelor's degree programs in higher educational institutions of some countries of Europe, North America and Australia, analyzes the algorithm of the educational process, the contents of the relevant curricula and other approaches to the organization of the educational process. The article substantiates the role of vocational training in physics in the context of the further development in the nuclear industry and many other areas of fundamental research. The emphasis is placed on the importance of comparative studies in the era of globalization. At the same time, particular attention is drawn to the fact that the vast majority of comparative studies highlight the processes in the general secondary education of the developed countries of the world. Meanwhile, insufficient attention is paid to the analysis of the main tendencies in vocational training of specialists with higher education in foreign universities, especially specialists in natural sciences. The paper also provides an analysis of doctoral research works on pedagogy that deal with the theory and methodology of vocational training of specialists in physics. The corresponding problem field is currently proved to be presented by few works which do not consider the phenomenon in full. The generalizations made in this paper are based on the analysis of Master's programs in physics and PhD programs that are being implemented at the Munich and Hamburg Universities (Germany), the Higher School of Ecole Normale (France), the United Kingdom's Nuclear Technology Education Consortium (which unites 12 universities), the Massachusetts Institute of Technology and the University of California (USA), Melbourne and Sydney Universities (Australia). The paper concludes that it is necessary to adopt a series of measures of managerial and educationalmethodological nature that will allow Ukraine to return the position of one of the leaders in providing higher education in the field of physics. The emphasis is put on signing bilateral agreements with foreign universities on the mutual exchange of faculty members who train future physicists and arrangements for student internships in leading European, North American and Australian laboratories.